Heavy Metals in Agricultural Soils - Taraczközi, Kamilla (Acta Agraria Debreceniensis, 2003)
The soil constitutes the basis of the food chain. To keep soil conditions in a good trim is very important, it’s part of the sustainable development and of producing food supply harmless to health.In some cases, soil productivity is the only important part, qualitative requirements or economical characteristics can improve it. The soil is threatened by two danger factors: the soil degradation and the soil pollution. The accumulation of different harmful and/or toxic substances in the soil is well known. Heavy metals constitute a part of it. Metals in the soil and in the soil-solution are balanced. This balance depends on the type of the metal, on the pH, on the cation-band capacity of the soil, on the redox relations and the concentration of cations in the soil.To be able to handle the metal contamination of the soil, it is important to estimate the form, the possible extension and the concentration of metals.Of course, the different types of soils have different physical-chemical, biological and buffer capacity, they can moderate or reinforce the harmful effects of heavy metals. To draw general conclusion of the dispersion and quantitative relations on the metals originated from different contamination sources is hard, because in some emissive sources contamination is limited in small areas but on a high level, some others usually expand on larger areas, and as a result of equal dispersion, the contamination’s level is lower.Heavy metals – unlike alkali ions – strongly bond to organic materials, or infiltrate in a kelát form. Their outstanding characteristic is the tendency to create metal-complex forms. Kelats take part in the uptaking and transportation of heavy metals. Heavy metals exert their effects mostly as enzyme-activators.The metals cannot degrade in an organic way, they accumulate in living organisms, and they can form toxic compounds through biochemical reactions.Lot of the heavy metals accumulate on the boundaries of the abiotic systems (air/soil, water/sediment), when physical or chemical parameters change, and this influences their remobilization.Human activity plays a great part in heavy metal mobilization, results in the human origin of most biochemical process of metals.To understand the toxic influence of accumulated metals of high concentration, their transportation from soils to plants or their damage in human health, must clearly defined and investigated.For effective protection against soil pollution, the types and levels of harmful pollution to soil must identified, regarding legal, technical and soil-science aspects, preferable in a single way. Difficulties in this area mean that toxicity depends on loading, uptake, soil characteristics and living organisms (species, age, condition etc.), furthermore, local and economic conditions considerably differ.